Peasants’ Motivations to Maintain Vegetation of Tropical Dry Forests in Traditional Agroforestry Systems from Cuicatlán, Oaxaca, Mexico - Rendón-Sandoval, Francisco J.; Casas, Alejandro; Sinco-Ramos, Perla G.; García-Frapolli, Eduardo; Moreno-Calles, Ana I. (Frontiers in Environmental Science, 2021)
The ways traditional rural communities conduct activities to meet their livelihoods commonly contribute to conservation of biodiversity and ecosystem functions. Traditional agroforestry systems (TAFS) are expressions of management that deliberately retain wild vegetation coexisting with crops to obtain multiple socio-ecological contributions. However, processes enhancing productive intensification endanger their permanence. This study aimed to 1) identify the peasants’ motivations to maintain the vegetation of tropical dry forest within their agricultural fields, 2) analyze the capacity of TAFS to provide contributions to people’s well-being, and 3) identify factors and processes limiting conservation capacities and possible alternatives. The study was conducted in three communities of the Tehuacán-Cuicatlán Valley, Oaxaca, Mexico. We performed a qualitative analysis with information from two workshops with local people, 10 semi-structured interviews with managers of TAFS, participant observation, complementary informal talks, and fieldwork notes. For analyzing the data, we: 1) generated a list of central themes based on the data collected, 2) established preliminary categories of such themes, 3) coded all information through the Atlas. ti software, 4) adjusted the classification of categories and codes to the data, 5) grouped codes and analyzed their relationships. We found that the peasants’ motivations to maintain the wild vegetation are the provision of multiple beneficial contributions: material (edible fruit, medicinal plants, fodder, firewood), regulating (shade, soil fertility, humidity keeping, rain attraction), and nonmaterial (regional flavors, ornamental, ritual), among others, which meet some of their fundamental needs (primarily subsistence, identity, and protection). The main reasons for keeping the wild vegetation were material contributions (62%). Also, we observed that TAFS safeguarding a higher forest cover and species diversity provide a broader range of socio-ecological contributions and potential to satisfy human needs than those with lower cover. Peasant agriculture may allow maintaining biodiversity while satisfying fundamental human needs. However, it needs to be revitalized, made more efficient, profitable, and dignified. The agroecological management implemented by peasants in TAFS is crucial for ensuring the continuity of essential environmental functions and people’s well-being.